The Influence of Communication in Increasing Work Productivity at PT. Global Technomedica Mandiri Pekanbaru - Defitri, Wanda; Dani, Dani (First Ciera Publisher, 2024)
This research was conducted at PT. Global Teknomedika Mandiri Pekanbaru, the respondents of this study were 31 people, where the sample of this study were employees of PT. Global Teknomedika Mandiri Pekanbaru. The purpose of this study was to determine the Effect of Communication on Work Productivity at PT. Global Teknomedika Mandiri Pekanbaru with the results of the hypothesis test showing that t count (7.646)> t table (2.0452) with sig 0.000 <sig 0.05, so it can be concluded that there is a significant influence on if Communication on Productivity at PT. Global Teknomedika Mandiri Pekanbaru. The conclusion of this study is that the Communication variable affects the Work Productivity variable at PT. Global Teknomedika Mandiri Pekanbaru.